2017
DOI: 10.1016/j.abrep.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Swedish version of the short UPPS-P impulsive behavior scale among young adults

Abstract: The UPPS-P model of impulsivity proposes that impulsivity comprises five distinct facets—negative urgency, positive urgency, lack of premeditation, lack of perseverance, and sensation seeking. The UPPS-P Impulsive Behavior Scale has been used to measure these facets. The purpose of the current study was to develop and evaluate the psychometric properties of a Swedish version of the 20-item UPPS-P Impulsive Behavior Scale (SUPPS-P). The sample comprised 343 Swedish young adults (Mage = 24.21, SD = 2.01; 27% men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 25 publications
3
22
0
7
Order By: Relevance
“…Moreover, males scored significantly higher on sensation seeking than did females, which was in accordance with previous research findings (8,10,13,14). However, some studies found that males scored higher than females on positive and negative urgency, but the results of other studies were the opposite (8,10,13,14,31). That our study gave different results may be because of the unbalanced sample in terms of gender.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, males scored significantly higher on sensation seeking than did females, which was in accordance with previous research findings (8,10,13,14). However, some studies found that males scored higher than females on positive and negative urgency, but the results of other studies were the opposite (8,10,13,14,31). That our study gave different results may be because of the unbalanced sample in terms of gender.…”
Section: Discussionsupporting
confidence: 91%
“…For example, negative urgency was associated with aggression and lack of premeditation, and positive urgency was associated with smoking status, while sensation seeking and lack of perseverance were associated with problematic use of alcohol (7). There are also gender differences in impulsivity, such that studies show consistently higher levels of sensation seeking in males than females (8)(9)(10)(11)(12)(13)(14). However, there are mixed results for gender differences in the other four UPPS-P facets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated gender differences in specific UPPS-S dimensions and therefore hypothesised that women would gain lower results than men in the sensation seeking and positive urgency subscales, and higher results in the negative urgency subscale [14,24]. A positive verification of this hypothesis will confirm the measure validity of the impulsivity aspects dependent on gender differences.…”
Section: ■ Cel Badań I Hipotezymentioning
confidence: 72%
“…Many of the items in the five subscales reach redundancy indicators [17]. This is why many shortened versions of the tool have been created as SUPPS-P (French [18], English [19], Spanish [21], Italian [23] and Swedish [24]). The aim of this study was to develop and validate the Polish version of SUPPS-P, which would be useful both for empirical studies and for clinical purposes.…”
Section: ■ Study Aim and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation